Effect of Thematic Teaching Strategy on Secondary School Physics Students’ Achievement in Ilorin, Kwara State. - IBRAHIM, Abdulwaheed Opeyemi (Ilorin Journal of Education, 2023)
This study determined the effect of thematic teaching strategy on secondary school physics Students’ achievement in Ilorin Kwara State, Nigeria. Quasi-experimental design was adopted for the study. The sample size for the study comprised of 258 SSII Physics Students from four co-educational secondary schools that were purposively selected from one of the three senatorial zone in Kwara State. The topics were taught based on thematic teaching strategy. The data were collected using Physics Achievement Test (PAT). Pearson Product Moment Correlation (PPMC) formula was used to determined reliability coefficient and a value of 0.86 coefficient was obtained. Mean, standard deviation, analysis of variance and analysis of covariance (ANCOVA) were used for data analysis. The finding of the study indicates that, experimental group perform better than those in control group among others. It was recommended that, thematic mode of teaching strategy should be include to secondary school curriculum and syllabus.